REGRESI LINEAR BIVARIAT SIMPEL DAN APLIKASINYA PADA DATA CUACA DI CILACAP - Saniyah Saniyah; Budi Pratikno (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2014)
This study discusses the simple bivariate linear regression on weather data in Cilacap district. This simple bivariate linear regression using the two response variables, rainfall () and humidity of an area (), and one predictor variable, the air temperature (). Regression model test method is a Wilk's Lamda test, the value of Wilk's Lamda = 0.881101 less than lambda table 0.903. The results show that the model and the both parameters are significant, with mean deviation error model is .